Method for separating and recovering silicon and aluminum elements from coal gangue
The coal gangue is activated by high-temperature roasting of solid fluorinating agent, and combined with alkali desilicate and acid-enhancing aluminum extraction processes, the problems of high energy consumption and environmental pollution in the extraction of silicon-aluminum elements in coal gangue in the prior art are solved, and efficient and environmentally friendly silicon-aluminum elements are achieved.
Patent Information
- Application Number
- CN202510107170.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art has problems of high energy consumption, environmental pollution and low extraction efficiency when extracting silicon and aluminum elements from coal gangue, especially the calcination method and melting method can produce greenhouse gas emissions and smoke pollution.
The coal gangue is activated by high-temperature roasting of solid fluorinated agents to generate soluble fluorosilicate and fluoroaluminum compounds. Combined with the processes of alkali desilicate and acid extraction of aluminum, the efficient separation and recovery of silicon and aluminum through ball milling, drying, roasting, alkaline and acid dissolution.
It significantly reduces the stability of silicon-aluminum minerals in coal gangue, improves the selective leaching and separation efficiency of silicon-aluminum, and realizes efficient, environmentally friendly and energy-saving silicon-aluminum element recycling, reducing environmental pollution and subsequent treatment complexity.
Smart Images

Figure CN119822374A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of coal gangue resource utilization, and specifically discloses a method for separating and recovering silicon and aluminum elements from coal gangue. Background Art
[0002] Coal gangue is solid waste from coal mining and processing. Long-term accumulation will occupy a large amount of land resources, and its seepage will pollute the environment. Therefore, extracting silicon and aluminum from coal gangue can not only effectively reduce waste accumulation, but also achieve high-value utilization of solid waste resources and reduce negative impacts on the environment.
[0003] In recent years, the comprehensive utilization rate of coal gangue has gradually increased, and a variety of processes have been developed to extract mineral resources from coal gangue to prepare chemical products. The processes can be roughly divided into acid method and alkaline method. The acid method can effectively dissolve silicon aluminum oxides in coal gangue, has high reaction efficiency, and is suitable for large-scale industrial extraction. However, the acid method easily produces a large amount of acidic waste liquid, and improper treatment will cause environmental pollution. The alkaline process is relatively simple and suitable for large-scale treatment. The alkaline waste liquid is relatively easy to handle. The extracted aluminum product has a higher purity and the process is more environmentally friendly. However, the alkali consumption is large, the efficiency of silicon extraction is low, and a large amount of alkaline waste liquid will be generated during the extraction process, which requires subsequent treatment.
[0004] At present, there have been many studies that combine the acid method with the alkali method. This technology first uses calcination activation. Through the calcination process, high temperature is used to activate the mineral components in the gangue, destroy its crystal structure, increase the surface area, and thus improve the reaction efficiency of the acid-base solvent. During the calcination process, additives can also be added to enhance the activation effect. The most commonly used additive is sodium carbonate. The sodium oxide decomposed during the calcination process has a fluxing effect, which can promote the destruction of the gangue mineral crystals and improve the dissolution efficiency. However, a higher temperature is required to decompose the carbonate, which consumes a lot of energy; some products may remain in the solution, affecting the extraction purity. The acid-base combined technology can achieve the comprehensive extraction of silicon and aluminum elements in gangue by adjusting the activation method. However, the calcination method and the melting method will also produce greenhouse gas emissions and smoke pollution. Therefore, there is an urgent need for a simple, efficient, highly selective, environmentally friendly and energy-saving method to extract valuable elements from gangue. Summary of the invention
[0005] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a simple, efficient, highly selective, environmentally friendly and energy-saving method for extracting valuable elements from coal gangue, thereby realizing the recovery of valuable elements in coal gangue. To achieve the above purpose, the present invention adopts the following technical solutions:
[0006] The method for comprehensive extraction and efficient separation of silicon and aluminum elements in coal gangue comprises the following steps:
[0007] (1) Pretreatment of coal gangue: The coal gangue raw material is crushed, put into a ball mill, and then passed through a 100-mesh sieve and dried to obtain pretreated coal gangue powder.
[0008] (2) Activation treatment of coal gangue: The pretreated coal gangue powder is fully mixed with the activation aid and then placed in a muffle furnace for heating and roasting, and the heat is maintained to obtain a roasted product.
[0009] The activation aid is ammonium fluoride; the addition amount is 2-10wt% of the total mass of the coal gangue; the heating and roasting temperature is 500-800°C, and the insulation time is 1-3h;
[0010] The amount of fluorinating agent added is preferably 5wt% of the total mass of the coal gangue, the heating and calcining temperature is preferably 700°C, and the holding time is preferably 2h;
[0011] (3) Alkali desiliconization: The calcined activated coal gangue powder is mixed with 3M NaOH solution at a liquid-solid ratio of 5mL / g to 15mL / g, and then the mixture is heated and stirred in a water bath (temperature of 60°C to 120°C, heating time of 2h to 5h). During the alkaline desiliconization process, an auxiliary agent and an adsorbent are added, and the stirring speed is 400rpm to achieve silicon leaching. After the leaching is completed, the leachate is passed through a 0.45μm hydrophilic PTFE filter membrane to obtain a silicon-rich leachate.
[0012] The addition amount of the auxiliary agent and the adsorbent is 5-10wt% of the total mass of the coal gangue.
[0013] (4) Acid extraction of aluminum: Dry and grind the aluminum-rich leaching residue and mix it with HCl solution (solution concentration is 3M) at a liquid-solid ratio of 5mL / g to 15mL / g, then heat it in a water bath at a temperature of 50°C to 90°C, a heating time of 2h to 3h, a stirring speed of 400rpm, and ultrasonic assisted leaching, with an ultrasonic power of 300W and an ultrasonic time of 30min, and each ultrasonic treatment lasts for 5min and then stands for 1min. The leachate is filtered through a 0.45μm hydrophilic PTFE filter to obtain an aluminum-rich leachate.
[0014] The beneficial effects of the present invention are as follows:
[0015] (1) The present invention activates coal gangue by high-temperature roasting with a solid fluorinating agent to generate soluble fluorosilicates (H2SiF6) and fluoroaluminum compounds (AlF3), which significantly reduces the stability of silicon-aluminum minerals in the coal gangue, promotes the selective leaching of silicon and aluminum, and realizes efficient separation of silicon and aluminum.
[0016] (2) The present invention adds sodium carbonate and activated carbon during the alkaline dissolution process, which can not only effectively improve the dissolution efficiency of silicon and the separation effect of silicon and aluminum, but also reduce the complexity of subsequent treatment of the solution and reduce the cost of the separation and purification process. It provides a more efficient, economical and environmentally friendly solution for the resource utilization of coal gangue. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0018] In order to make the above-mentioned objects, features and advantages of the present invention more clearly understood, the specific implementation modes of the present invention are described in detail below in conjunction with embodiments.
[0019] Example 1
[0020] The coal gangue was crushed and ball-milled and then passed through a 100-mesh sieve. The sieved coal gangue was dried at 105°C for 8 hours. Weigh 1g of coal gangue powder containing 52.8% silicon dioxide and 30.22% aluminum oxide and mix it with 0.05g of ammonium fluoride, place it in a porcelain ark, and then raise the temperature to 700°C at a heating rate of 5°C / min, maintain it at this temperature for 2h, and take out the calcined product after it drops to room temperature. The calcined product is leached with 3M sodium hydroxide solution for pre-desiliconization. During the alkali dissolution process, 0.05g of sodium carbonate and 0.05g of activated carbon are added, the leaching liquid-solid ratio is 10mL / g, the leaching temperature is 90°C, the leaching time is 3h, and the silicon-containing leaching liquid and aluminum-rich leaching slag are filtered; the obtained aluminum-rich leaching slag is washed, dried and ground, and aluminum is leached with 3M hydrochloric acid solution, the leaching liquid-solid ratio is 10mL / g, the leaching temperature is 70°C, the leaching time is 2h, combined with ultrasonic assisted acid leaching, the ultrasonic power is 300W, the ultrasonic time is 30min, and each ultrasonic 5min is allowed to stand for 1min. After leaching, the aluminum-containing leaching solution is filtered and precipitated by multi-stage pH control distribution, and calcined to produce alumina. The concentration of silicon and aluminum in the filtrate is determined by ultraviolet spectrophotometer and the leaching rate is calculated.
[0021] The concentration of silicon ions in the filtrate was measured by ultraviolet spectrophotometer, and the leaching rate η of silicon ions was calculated using formula (1).
[0022]
[0023] Where: c is the concentration of silicon in the leachate, mg / L. V is the volume of the leachate, mL. m is the mass of the added gangue powder, g. W0 is the mass fraction of silicon in the original gangue powder, wt%.
[0024] The concentration of aluminum ions in the filtrate was measured by ultraviolet spectrophotometer, and the aluminum ion leaching rate η was calculated using formula (2).
[0025]
[0026] Where: c is the concentration of aluminum in the leachate, mg / L. V is the volume of the leachate, mL. m is the mass of the added gangue powder, g. W0 is the mass fraction of aluminum in the original gangue powder, wt%.
[0027] Example 2
[0028] The difference between this embodiment and embodiment 1 is that, in the activation process, the amount of ammonium fluoride added is 0.02 g, and the rest of the preparation process and leaching process are the same as those of embodiment 1. The concentrations of silicon and aluminum in the filtrate are measured by ultraviolet spectrophotometer and the leaching rate is calculated.
[0029] Example 3
[0030] The difference between this embodiment and embodiment 1 is that, during the activation process, the amount of ammonium fluoride added is 0.08 g, and the rest of the preparation process and leaching process are the same as those of embodiment 1. The concentrations of silicon and aluminum in the filtrate are measured by ultraviolet spectrophotometer and the leaching rate is calculated.
[0031] Example 4
[0032] The difference between this embodiment and embodiment 1 is that, during the activation process, the amount of ammonium fluoride added is 0.1 g, and the rest of the preparation process and leaching process are the same as those of embodiment 1. An ultraviolet spectrophotometer is used to measure the concentration of silicon and aluminum in the filtrate and calculate the leaching rate.
[0033] Comparative Example 1
[0034] The difference between this comparative example and Example 1 is that, during the activation process, no activation aid is added, and the activation is directly calcined, and the rest of the preparation process and leaching process are the same as Example 1. The concentrations of silicon and aluminum in the filtrate are measured by ultraviolet spectrophotometer and the leaching rate is calculated.
[0035] The leaching rates of silicon and aluminum in the above examples and comparative examples were calculated and compared with those in Example 1, and the results are shown in Table 1.
[0036] Table 1 Effect of different amounts of ammonium fluoride as an activation aid on the leaching rate of silicon and aluminum
[0037]
[0038] It can be seen from Table 1 that when calcined activated coal gangue is used directly, the leaching rate of silicon is much lower than the leaching rate using ammonium fluoride as an activation additive. The reason may be that ammonium fluoride, as an activation aid, converts the silicon dioxide in the coal gangue into soluble fluorosilicates through fluorination, which promotes the dissolution of silicon and the extraction efficiency in the subsequent leaching process. For the extraction of aluminum, although ammonium fluoride also has a promoting effect, its improvement effect is relatively small compared to silicon. According to Examples 2 to 4, when the amount of ammonium fluoride added increases, excessive fluoride ions may cause fluoride precipitation or the formation of insoluble complexes, inhibiting the dissolution and leaching of silicon. Therefore, the following examples select the addition of ammonium fluoride as 5wt% of the total mass of coal gangue.
[0039] Comparative Example 2
[0040] The difference between this comparative example and Example 1 is that during the activation process, the activation aid added is calcium fluoride for calcination activation, and the rest of the preparation process and leaching process are the same as Example 1. The concentrations of silicon and aluminum in the filtrate are measured by ultraviolet spectrophotometer and the leaching rate is calculated.
[0041] Comparative Example 3
[0042] The difference between this comparative example and Example 1 is that, during the activation process, the added activation aid is sodium fluoride for calcination activation, and the rest of the preparation process and leaching process are the same as Example 1. The concentrations of silicon and aluminum in the filtrate are measured by ultraviolet spectrophotometer and the leaching rate is calculated.
[0043] Table 2 Effect of different activation aids on silicon and aluminum leaching rates
[0044]
[0045] As can be seen from Table 2, when calcium fluoride or sodium fluoride is used as an activation aid to calcine coal gangue, the leaching rate of silicon is significantly lower than that when ammonium fluoride is used. The reason may be that the reaction activity of calcium fluoride is low, and a higher roasting temperature is required to effectively promote its reaction with minerals in coal gangue. Although sodium fluoride has good chemical stability and can react with Si and Al compounds in coal gangue to generate corresponding fluorides, its reaction efficiency is slightly lower than that of ammonium fluoride, and the roasting temperature and time need to be further optimized to improve the leaching effect.
[0046] Example 5
[0047] The difference between this embodiment and embodiment 1 is that the calcination activation temperature is 600° C., and the rest of the preparation process and leaching process are the same as those of embodiment 1. The concentrations of silicon and aluminum in the filtrate are measured by ultraviolet spectrophotometer and the leaching rate is calculated.
[0048] Example 6
[0049] The difference between this embodiment and embodiment 1 is that the calcination activation temperature is 800° C., and the rest of the preparation process and leaching process are the same as those of embodiment 1. An ultraviolet spectrophotometer is used to measure the concentration of silicon and aluminum in the filtrate and calculate the leaching rate.
[0050] The leaching rates of silicon and aluminum in the above examples were calculated and compared with those in Example 1, and the results are shown in Table 3.
[0051] Table 3 Effect of different calcination activation temperatures on silicon and aluminum leaching rates
[0052]
[0053] It can be seen from Table 3 that the best calcination temperature is 700°C, at which the leaching rate of silicon and aluminum is ideal. When the temperature is too low (600°C), the activation degree of the mineral is insufficient, resulting in low leaching efficiency; when the temperature is too high (800°C), although the leaching rate of silicon and aluminum is improved, there may be side reactions or the generation of insoluble compounds, which reduces the leaching efficiency of silicon. Therefore, the calcination activation temperature selected in the following examples is 700°C.
[0054] Example 7
[0055] The difference between this embodiment and embodiment 1 is that the amount of sodium carbonate and activated carbon added in the alkaline dissolution process is 0.1 g, and the rest of the preparation process and leaching process are the same as those in embodiment 1. The concentrations of silicon and aluminum in the filtrate are measured by ultraviolet spectrophotometer and the leaching rate is calculated.
[0056] Comparative Example 4
[0057] The difference between this comparative example and Example 1 is that no reagent is added during the alkali dissolution process, and the coal gangue powder is directly leached using sodium hydroxide solution, and the rest of the process is the same as Example 1. The concentrations of silicon and aluminum in the filtrate are measured using an ultraviolet spectrophotometer and the leaching rate is calculated.
[0058] Comparative Example 5
[0059] The difference between this comparative example and Example 1 is that only 0.05 g of sodium carbonate is added during the alkali dissolution process, and the rest of the process is the same as Example 1. The concentrations of silicon and aluminum in the filtrate are measured by an ultraviolet spectrophotometer and the leaching rates are calculated.
[0060] Comparative Example 6
[0061] The difference between this comparative example and Example 1 is that only 0.05 g of activated carbon is added as an adsorbent during the alkali dissolution process, and the rest of the process is the same as Example 1. The concentrations of silicon and aluminum in the filtrate are measured using an ultraviolet spectrophotometer and the leaching rates are calculated.
[0062] The leaching rates of silicon and aluminum in the above examples and comparative examples were calculated and compared with those in Example 1, and the results are shown in Table 4.
[0063] Table 4 Effect of different drug addition amounts on silicon and aluminum leaching rates during alkaline dissolution
[0064]
[0065] It can be seen from Table 4 that when the gangue powder is directly leached with sodium hydroxide solution without adding any reagents, the leaching rate of silicon ions is much lower than the leaching rate of adding reagents. Sodium carbonate can enhance the alkaline environment, cooperate with sodium hydroxide to improve the dissolution efficiency of silicon, and form sodium silicate with silicon dioxide. The addition of activated carbon can adsorb impurity metals and reduce their interference with silicon, thereby further improving the leaching rate of silicon. Therefore, the amount of sodium carbonate and activated carbon added in the following examples is selected to be 5wt% of the total mass of the gangue powder.
[0066] Example 8
[0067] The difference between this embodiment and embodiment 1 is that the temperature of the water bath during the alkali desiliconization process is 60° C., and the other reaction conditions are exactly the same as those of embodiment 1. The concentrations of silicon and aluminum in the filtrate are determined by an ultraviolet spectrophotometer and the leaching rate is calculated.
[0068] Example 9
[0069] The difference between this embodiment and embodiment 1 is that the temperature of the oil bath during the alkali desiliconization process is 120° C., and the other reaction conditions are exactly the same as those of embodiment 1. The concentrations of silicon and aluminum in the filtrate are measured by an ultraviolet spectrophotometer and the leaching rate is calculated.
[0070] The leaching rates of silicon and aluminum in the above examples were calculated and compared with those in Example 1, and the results are shown in Table 5.
[0071] Table 5 Effect of different leaching temperatures on silicon and aluminum leaching rates
[0072]
[0073] It can be seen from Table 5 that temperature has a significant effect on the leaching rate of silicon and aluminum elements. As the temperature increases, the leaching rate of silicon is relatively high, indicating that the activation effect of the alkaline solution on the coal gangue at high temperature is more sufficient, which promotes the leaching of silicon. However, when the oil bath temperature reaches 120°C, the leaching rate of silicon decreases, which may be because the silicate ions that have been dissolved at high temperature may re-form polymers and secondary precipitation, reducing the leaching rate of silicon. Therefore, the leaching temperature selected in the following examples is 90°C.
[0074] Example 10
[0075] The difference between this embodiment and embodiment 1 is that the water bath heating time during the alkali desiliconization leaching process is 2 hours, and the other reaction conditions are exactly the same as those in embodiment 1. The concentrations of silicon and aluminum in the filtrate are determined by an ultraviolet spectrophotometer and the leaching rate is calculated.
[0076] Embodiment 11
[0077] The difference between this embodiment and embodiment 1 is that the water bath heating time during the alkali desiliconization leaching process is 5 hours, and the other reaction conditions are exactly the same as those of embodiment 1. The concentrations of silicon and aluminum in the filtrate are determined by an ultraviolet spectrophotometer and the leaching rate is calculated.
[0078] The leaching rates of silicon and aluminum in the above examples were calculated and compared with those in Example 1, and the results are shown in Table 6.
[0079] Table 6 Effect of different leaching time on silicon and aluminum leaching rate
[0080]
[0081] Table 6 shows that as the leaching time gradually increases from 2h to 5h, the leaching rate of silicon and aluminum elements gradually increases. When the leaching time is short, it is not enough to completely leach the silicon element in the coal gangue. As the leaching time increases, the leaching rate gradually tends to balance, and the leaching reaction of the surface coal gangue powder reaches equilibrium. Therefore, considering economic factors comprehensively, the leaching time selected in the following examples is 3h.
[0082] Example 12
[0083] The difference between this embodiment and embodiment 1 is that the liquid-to-solid ratio of the sodium hydroxide solution to the calcined activated coal gangue powder is 5 mL / g, and the other reaction conditions are exactly the same as those of embodiment 1. The concentrations of silicon and aluminum in the filtrate are determined by an ultraviolet spectrophotometer and their leaching rates are calculated.
[0084] Example 13
[0085] The difference between this embodiment and embodiment 1 is that the liquid-to-solid ratio of the sodium hydroxide solution to the calcined activated coal gangue powder is 15 mL / g, and the other reaction conditions are exactly the same as those of embodiment 1. The concentrations of silicon and aluminum in the filtrate are determined by an ultraviolet spectrophotometer and their leaching rates are calculated.
[0086] The silicon and aluminum leaching rates in the above examples were calculated and compared with those in Example 1, and the results are shown in Table 7.
[0087] Table 7 Effect of different liquid-solid ratios on silicon and aluminum leaching rates
[0088]
[0089] Table 7 reflects the effect of the liquid-to-solid ratio of sodium hydroxide solution to calcined activated coal gangue powder on the leaching efficiency. It can be seen that when the liquid-to-solid ratio is 10mL / g and 15mL / g, both have good leaching rates. When the liquid-to-solid ratio is only 5mL / g, the leaching rate decreases. The reason is that a too low liquid-to-solid ratio may lead to an excessively high solution concentration, resulting in limited dissolution reaction and affecting the adequacy of the reaction. Therefore, after comprehensive consideration, a liquid-to-solid ratio of 10mL / g is selected as the optimal liquid-to-solid ratio of this method.
[0090] Embodiment 14
[0091] The difference between this embodiment and embodiment 1 is that during the leaching of aluminum with hydrochloric acid solution, the temperature of the water bath is 90° C., and the other reaction conditions are exactly the same as those in embodiment 1. The concentration of aluminum in the filtrate is determined by an ultraviolet spectrophotometer and its leaching rate is calculated.
[0092] Embodiment 15
[0093] The difference between this embodiment and embodiment 1 is that during the leaching of aluminum with hydrochloric acid solution, the temperature of the water bath is 50° C., and the other reaction conditions are exactly the same as those in embodiment 1. The concentration of aluminum in the filtrate is measured by ultraviolet spectrophotometer and its leaching rate is calculated.
[0094] The silicon and aluminum leaching rates in the above examples were calculated and compared with those in Example 1, and the results are shown in Table 8.
[0095] Table 8 Effect of different leaching temperatures on aluminum leaching rate
[0096]
[0097] It can be seen from Table 8 that too low a temperature may cause a significant decrease in the leaching rate of aluminum. As the temperature increases, the solubility and reaction rate of aluminum increase, but the leaching rate of aluminum does not increase significantly. At a lower temperature, hydrochloric acid reacts slowly with minerals, resulting in a significant decrease in the dissolution efficiency of aluminum. Therefore, considering economic factors and energy consumption, the leaching temperature selected in the following examples is 70°C.
[0098] Example 16
[0099] The difference between this embodiment and embodiment 1 is that during the aluminum leaching process with hydrochloric acid solution, the liquid-to-solid ratio of the hydrochloric acid solution to the aluminum-rich leaching slag is 5 g / mL, and the other reaction conditions are exactly the same as those in embodiment 1. The aluminum concentration in the filtrate is determined by an ultraviolet spectrophotometer and its leaching rate is calculated.
[0100] Embodiment 17
[0101] The difference between this embodiment and embodiment 1 is that during the aluminum leaching process with hydrochloric acid solution, the liquid-to-solid ratio of the hydrochloric acid solution to the aluminum-rich leaching slag is 15 g / mL, and the other reaction conditions are exactly the same as those in embodiment 1. The aluminum concentration in the filtrate is determined by an ultraviolet spectrophotometer and its leaching rate is calculated.
[0102] The silicon and aluminum leaching rates in the above examples were calculated and compared with those in Example 1, and the results are shown in Table 9.
[0103] Table 9 Effect of different liquid-solid ratios on aluminum leaching rate
[0104]
[0105] Table 9 reflects the effect of the liquid-to-solid ratio of hydrochloric acid solution to aluminum-rich leaching slag on the leaching efficiency. It can be seen that both the liquid-to-solid ratio of 10mL / g and 15mL / g have good leaching rates. However, when the liquid-to-solid ratio is only 5mL / g, the leaching rate decreases. The reason may be that too low a solid powder concentration will affect the mass transfer coefficient of the reaction system, resulting in a decrease in the leaching rate of the aluminum element. Therefore, after comprehensive consideration, a liquid-to-solid ratio of 10mL / g is selected as the optimal liquid-to-solid ratio of this method.
[0106] It should be noted that the above embodiments are only used to illustrate the technical methods of the present invention rather than to limit them. Although experiments and analyses are performed with reference to the specific conditions and operating steps in the above embodiments, the scope of the present invention is not limited to these embodiments. Technicians can make appropriate modifications and optimizations to the embodiments based on the principles and ideas of the present invention without departing from the spirit and scope of the present invention.
Claims
1. A method for separating and recovering silicon and aluminum elements from coal gangue, characterized in that: The method steps are as follows: (1) crushing and ball-milling coal gangue and then passing it through a 100-mesh sieve; fully mixing the sieved coal gangue with an activation aid, ammonium fluoride, and then heating and roasting in a muffle furnace to obtain a roasted product; (2) the calcined product obtained in step (1) and the sodium hydroxide solution are uniformly mixed and then heated in a water bath for alkali desiliconization, during which an auxiliary agent and an adsorbent are added; the leachate is filtered through a 0.45 μm hydrophilic PTFE filter membrane to obtain a silicon-rich leachate, leaving an aluminum-rich leach residue; (3) The aluminum-rich leaching residue of step (2) is dried, ground, and mixed evenly with a hydrochloric acid solution, and then heated in a water bath for ultrasonic-assisted leaching. The leachate is filtered through a 0.45 μm hydrophilic PTFE filter membrane to obtain an aluminum-rich leachate.
2. The method for separating and recovering silicon and aluminum elements from coal gangue according to claim 1, characterized in that: The amount of the activation aid added in step (1) is 2 to 10 wt % of the total mass of the coal gangue.
3. The method for separating and recovering silicon and aluminum elements from coal gangue according to claim 1, characterized in that: The calcination temperature in step (1) is 500-800° C. and the calcination time is 1-3 hours.
4. The method for separating and recovering silicon and aluminum elements from coal gangue according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in step (2) is 3M, and the solid-liquid ratio of alkali desiliconization is 5-15 g / mL.
5. The method for separating and recovering silicon and aluminum elements from coal gangue according to claim 1, characterized in that: In step (2), the auxiliary agent is sodium carbonate and the adsorbent is activated carbon, and the added amounts are 5-10wt% of the total mass of the coal gangue.
6. The method for separating and recovering silicon and aluminum elements from coal gangue according to claim 1, characterized in that: The alkali desiliconization heating temperature in step (2) is 60 to 120° C., and the alkali desiliconization heating time is 2 to 5 hours.
7. The method for separating and recovering silicon and aluminum elements from coal gangue according to claim 1, characterized in that: The solid-liquid ratio of the water bath heating ultrasound-assisted leaching in step (3) is 5-15 g / mL, and the concentration of the hydrochloric acid solution is 3M.
8. The method for separating and recovering silicon and aluminum elements from coal gangue according to claim 1, characterized in that: The ultrasonic-assisted leaching heating temperature in step (3) is 50 to 90° C., and the ultrasonic-assisted leaching heating time is 2 to 3 hours.
9. The method for separating and recovering silicon and aluminum elements from coal gangue according to claim 1, characterized in that: The water bath heating ultrasonic assisted in step (3) has an ultrasonic power of 300 W and an ultrasonic time of 30 min. The ultrasonic treatment is performed for 5 min and then allowed to stand for 1 min.
Citation Information
Cited By
Method for preparing high-purity mullite through pretreatment-calcination coupling of coal gangue
CN121553956A
Method for preparing high-purity mullite by coupling coal gangue pretreatment and calcination
CN121553956B
A method for separating and recovering silicon and aluminum elements from coal gangue using in-situ activation in atmospheric pressure liquid phase
CN122561963A